Vocational competence formation for social work specialists - Kyrylenko, Valentina; Kolchenko, Katerina (Social Welfare: Interdisciplinary Approach, 2011)
In the present article vocational competence and professional expertise formation is analyzed. Definitions of “competence” and “expertise” are compared. Levels of professional expertise formation and ways of achieving it during academic training are explored. A research among bachelor’s and master’s degree students (“social work” graduates of Open International University of Human Development “Ukraine”) is described.
Keywords: competence; expertise; social work specialist; vocational competence; professional expertise